Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist - Razo-González, María (Zootaxa, 2018)
Adults of Trichoptera were collected in four sites in Santa Catarina Lachatao, Oaxaca, México, using black light traps and entomological nets. A total of 12 families, 23 genera, and 37 species were recorded. Four new species of Trichoptera: Wormaldia noveloi n. sp., Lepidostoma zapoteca n. sp., Phylloicus gomezi n. sp., and Ochrotrichia buenoi n. sp. are described and male genitalia are illustrated. Similarities and differences among these species and those in their respective genera are discussed. In addition, nineteen species are recorded for the first time for Oaxaca, bringing the number of known Trichoptera species from this state to 170. Ithytrichia, Oxyethira, and Cheumatopsyche are new generic records for Oaxaca State. Ochrotrichia nicaragua and Wormaldia palma are registered for the first time in México.